2011
DOI: 10.1542/peds.2011-0072
|View full text |Cite
|
Sign up to set email alerts
|

Decisions of Black Parents About Infant Bedding and Sleep Surfaces: A Qualitative Study

Abstract: OBJECTIVE: The goal of this qualitative study was to examine factors influencing decisions by black parents regarding use of soft bedding and sleep surfaces for their infants. METHODS: We conducted focus groups and individual interviews with black mothers of lower and higher socioeconomic status (SES). Mothers were asked about many infant care practices, including sleep surface and bedding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 40 publications
3
71
0
Order By: Relevance
“…Adult beds frequently have parental bedding (eg, blankets, pillows); in addition, many parents who sleep with their infant use bedding to build a barrier in the belief that the bedding will protect the infant from falling off the bed or from rollover accidents. 16 We also found that the majority of cribs contained soft or loose bedding. Many parents use soft bedding because of concerns about infant warmth and comfort, and to prevent infants from hurting themselves, and they may not be aware that soft bedding in the infant sleep environment creates a hazard.…”
Section: Discussionmentioning
confidence: 53%
“…Adult beds frequently have parental bedding (eg, blankets, pillows); in addition, many parents who sleep with their infant use bedding to build a barrier in the belief that the bedding will protect the infant from falling off the bed or from rollover accidents. 16 We also found that the majority of cribs contained soft or loose bedding. Many parents use soft bedding because of concerns about infant warmth and comfort, and to prevent infants from hurting themselves, and they may not be aware that soft bedding in the infant sleep environment creates a hazard.…”
Section: Discussionmentioning
confidence: 53%
“…Qualitative studies show that parents who use bedding want to provide a comfortable and safe environment for their infant. 236 For comfort, parents may use blankets to provide warmth or to soften the sleep surface. For safety, parents may use pillows as barriers to prevent falls from adult beds or sofas or as a prop to keep their infant on the side.…”
Section: Use Of Beddingmentioning
confidence: 99%
“…For safety, parents may use pillows as barriers to prevent falls from adult beds or sofas or as a prop to keep their infant on the side. 236 Images of infants sleeping with blankets, pillows, and other soft objects are widespread in popular magazines targeted to families with newborn infants. 237 Parents and caregivers who see these images may perceive the use of these items as the norm, both favorable and the ideal, for infant sleep.…”
Section: Use Of Beddingmentioning
confidence: 99%
“…Why do parents feel the need to use soft bedding? Qualitative studies 13 are helpful in this regard. The major reasons for using soft bedding are comfort/warmth and safety.…”
mentioning
confidence: 99%
“…If they cover the bedding tightly, so that the covering sheet is taut, they believe that they are following the "firm sleep surface" recommendation, while also making it more comfortable. 13 In addition, parents may be incorrectly interpreting the recommendation against using thick blankets or comforters as meaning only over the infant, rather than under as well.…”
mentioning
confidence: 99%